Polytechnic Journal Staff '08 - Frank Aston::::::photographer::: (1908)
Group portrait of Polytechnic Journal staff, 1907-08. Taken in studio. Seated: Earl Campbell, Ruth Gould, Ernest W. Curtis, Hazel May Griffith, George Albert Tilton; standing: Alfred C. Dixon, --, --, Rachael E. Ramage, George Calvin Hopkins.(1 card addressed to 'Miss Diana Kendall' signed 'Geo. Tilton')